Orchard Valley grooms - Macomber, Debbie; Macomber, Debbie; Macomber, Debbie (Don Mills, Ont. : MIRA, 2010)
Valerie rushes home to Orchard Valley, Oregon, when her father, David, suffers a heart attack. She and her two younger sisters, Stephanie and Norah, are gathering at his side, praying he'll live, fearing he'll die. At a time like this, falling in love with her father's heart surgeon is the last thing on Valerie's mind. Meanwhile Stephanie has other worries besides her father's health. She'd fled Orchard Valley three years earlier after her humiliating rejection by local journalist Charles Tomaselli. Now she's home, and it's not long before they begin reliving past battles--and renewing old feelings.
Valerie (c1992) -- Stephanie (c1992).
Keywords: Sisters -- Fiction; Single women -- Fiction; Fathers -- Death -- Fiction; Man-woman relationships -- Fiction; Oregon -- Fiction; Love stories